Enhancement of VLC to Sushisen Algorithms Using BER Performance of the FSK Communication Network - Senthil, P. (Asian Journal of Electrical Sciences, 2018)
In this article, wide menstruates a visible light verbal exchange (VLC) system upon eight meters fair space transmission based concerning a commercial LED yet a grantee between coalitions with an audio interface on a clever phone. The signal is in FSK modulation format. The profitable empirical accomplishment validates the probability regarding the proposed rule between future wi-fi communication networks.